2010
DOI: 10.1111/j.1349-7006.2009.01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor (SAHA) and repression of EZH2 synergistically inhibit proliferation of gallbladder carcinoma

Abstract: Polycomb group protein EZH2, frequently overexpressed in malignant tumors, is the catalytic subunit of polycomb repressive complex 2 (PRC2). PRC2 interacts with HDACs in transcriptional silencing and relates to tumor suppressor loss. We examined the expression of HDAC isoforms (HDAC 1 and 2) and EZH2, and evaluated the possible use of HDAC inhibitor suberoylanilide hydroxamic acid (SAHA) and EZH2 repressor for gallbladder carcinoma. We used 48 surgically resected gallbladders and cultures of human gallbladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 37 publications
(95 reference statements)
2
41
0
Order By: Relevance
“…The search for more specific epigenetic-based therapies has identified the histone methyltransferase inhibitor 3-deazaneplanocin A as having efficacy in decreasing EZH2 levels. This results in the inhibition of H3K27 methylation, the reactivation of polycomb target genes, including INK4A, and the induction of growth inhibition and apoptosis in tumour cells in vitro (Tan et al, 2007;Fiskus et al, 2009;Puppe et al, 2009;Hayden et al, 2010;Yamaguchi et al, 2010). However, the fact that EZH2 is known to be mutated and inactivated in myeloid disorders (Ernst et al, 2010) suggests that Transcriptional regulation of cellular senescence F Lanigan et al EZH2-targeting drugs may only be effective in a subset of tumour types.…”
Section: Perspectivesmentioning
confidence: 97%
“…The search for more specific epigenetic-based therapies has identified the histone methyltransferase inhibitor 3-deazaneplanocin A as having efficacy in decreasing EZH2 levels. This results in the inhibition of H3K27 methylation, the reactivation of polycomb target genes, including INK4A, and the induction of growth inhibition and apoptosis in tumour cells in vitro (Tan et al, 2007;Fiskus et al, 2009;Puppe et al, 2009;Hayden et al, 2010;Yamaguchi et al, 2010). However, the fact that EZH2 is known to be mutated and inactivated in myeloid disorders (Ernst et al, 2010) suggests that Transcriptional regulation of cellular senescence F Lanigan et al EZH2-targeting drugs may only be effective in a subset of tumour types.…”
Section: Perspectivesmentioning
confidence: 97%
“…Recent studies have shown that HDACis have the potential to inhibit carcinogenesis and fibrogenesis (2,(9)(10)(11)(12)(13)(14)(15). VPA, a semiselective HDACi (20), is widely prescribed for patients with epilepsy and psychiatric disorders and well tolerated by the majority of patients (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Histone acetylation and deacetylation is controlled by histone acetyltransferases and histone deacetylases. In recent years, histone deacetylase inhibitors (HDACis) showed anti-cancer activities and are, therefore, of clinical interest (9)(10)(11)(12). There are also several reports showing an antifibrogenic effect of HDACis, but the underlying mechanism is still unclear (2,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Although EZH2 is the catalytic subunit of the polycomb repressive complex 2 (PRC2), it is accompanied by other components including SUZ12, EED, and YY1. Consequently, treatment with DZNep results in the depletion of each of these PRC2 complex proteins and blocks the associated histone H3 lysine 27 methylation (Chase & Cross, 2011;Fiskus et al, 2009;Yamaguchi et al, 2010). Therefore, DZNep may interfere with normal physiological processes that require methyl transfer.…”
Section: Enhancer Of Zeste Homologmentioning
confidence: 99%
“…www.intechopen.com (Chase & Cross, 2011;Fiskus et al, 2009;Yamaguchi et al, 2010). Although EZH2 is the catalytic subunit of the polycomb repressive complex 2 (PRC2), it is accompanied by other components including SUZ12, EED, and YY1.…”
Section: Enhancer Of Zeste Homologmentioning
confidence: 99%